Development of Halide Perovskite Single Crystal for Radiation Detection Applications - Pan, Wanting; Wei, Haotong; Yang, Bai (Frontiers in Chemistry, 2020)
Preface: Recently, low-cost perovskite single crystals have attracted intensive attention due to their excellent optoelectronic properties and improved stability when compared to polycrystalline films for various applications, such as solar cells (Kojima et al., 2009; Lee et al., 2012; Tsai et al., 2016; Sahli et al., 2018), lasers (Gu et al., 2016; Veldhuis et al., 2016), radiation detection (Kim et al., 2017), and so on. The unique optoelectronic properties and low-cost growing processes for large-sized single crystals also make them greatly suitable for radiation detection. In this review, we summarize various synthesis methods of perovskite single crystals and introduced the high radiation detection performance of the perovskite single crystal. The advantages and limitations of halide perovskite single crystals as radiation detector candidates will be discussed in detail, and corresponding future development trends can be expected by overcoming current obstacles (Leijtens et al., 2018; Boyd et al., 2019), such as ion migration (Eames et al., 2015), stability, etc.